Characteristics of a helical array antenna radiating circularly polarized conical beam - Phongcharoenpanich, Chuwong; Lertwiriyaprapa, Titipong; Lamultree, Suthasinee; Wounchoum, Phairote; Kosulvit, Sompol; Krairiksh, Monai (My University, 2001)
The characteristics of a helical array antenna radiating circularly polarized conical beams were presented. Guidelines were provided for the antenna design to realize the desired directivity and elevation angle. The total fields radiated from each small helical antenna on the ground plane were combined to calculate the radiation pattern of the antenna. The radiation patterns were demonstrated for various parameters such as the array radius and the number of elements.